Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Possibly seismically triggered avalanches after the S1222a Marsquake and S1000a impact event - A. Lucas; I.J. Daubar; M. Le Teuff; C. Perrin; T. Kawamura; L. Posiolova; P. Lognonné; S. Rodriguez; D. Giardini; G. Sainton; A. Mangeney; A. McEwen (Icarus, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Challenges and opportunities in the use of ponds and pondscapes as Nature-based Solutions - M. Cuenca-Cambronero; M. Blicharska; J.-A. Perrin; T. A. Davidson; B. Oertli; M. Lago; M. Beklioglu; M. Meerhoff; M. Arim; J. Teixeira; L. De Meester; J. Biggs; et al. (Hydrobiologia, 2023)
Ponds and “pondscapes” (networks of ponds) are crucial habitats for biodiversity and for delivering multiple benefits to humans, so-called “Nature’s Contribution to People”, such as climate mitigation and adaptation to climate change, creation, and maintenance of habitat for biodiversity, water purification, flood mitigation and cultural benefits (e.g., recreational possibilities). However, ponds are not often considered as Nature-based Solutions to provide all these benefits. In addition, there is insufficient knowledge on how to manage and restore ponds to maximise their role to increase the resilience of ecosystems and society to climate change. To facilitate improved implementation of ponds as Nature-based Solutions for the delivery of a wide range of Nature Contributions to People, it is important to generate and integrate biodiversity, ecosystems, societal, economic and policy knowledge. Hence, there is a need for evidence-based guidance to support the broader use of ponds. Here, we review the role of ponds and pondscapes in delivering Nature’s Contributions to People and provide an overview of the challenges and opportunities for their broader implementation as Nature-based Solutions. Finally, we propose a conceptual framework that can help the implementation of pond Nature-based Solutions, and that outlines future research needs.

4500 years of morphological diversification in Western Europe wild boars (Sus scrofa) and the consequences of the Neolithic transition - T. Cucchi; H. Harbers; D. Neaux; M. Balasse; L. Garbé; D. Fiorillo; H. Bocherens; D. Drucker; C. Zanolli; R. Cornette; R.M. Arbogast; S. Bréhard; et al. (Quaternary Science Reviews, 2023)

Influence of glacial turbidity and climate on diatom communities in two Fjord Lakes (British Columbia, Canada) - Kathleen R. Laird; Cécilia Barouillet; Brian F. Cumming; Christopher J. Perrin; Daniel T. Selbie (Aquatic Sciences, 2021)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Investigation of recharge dynamics and flow paths in a fractured crystalline aquifer in semi-arid India using borehole logs: implications for managed aquifer recharge - M. Alazard; A. Boisson; J-C. Maréchal; J. Perrin; B. Dewandel; T. Schwarz; M. Pettenati; G. Picot-Colbeaux; W. Kloppman; S. Ahmed (Hydrogeology Journal, 2016)

Hydrology under change: an evaluation protocol to investigate how hydrological models deal with changing catchments - G. Thirel; V. Andréassian; C. Perrin; J.-N. Audouy; L. Berthet; P. Edwards; N. Folton; C. Furusho; A. Kuentz; J. Lerat; G. Lindström; E. Martin; et al. (Hydrological Sciences Journal, 2015)

Does life history predict past and current connectivity for rocky intertidal invertebrates across a marine biogeographic barrier? - D. J. AYRE; T. E. MINCHINTON; C. PERRIN (Molecular Ecology, 2009)
The southeast Australian coast potentially includes a complex biogeographic barrier, largely lacking exposed rocky shore that may limit the dispersal of rocky intertidal taxa and contribute to the maintenance of two biogeographic regions. Surprisingly, within the 300‐km barrier region, several species considered exposed rocky shore specialists occurred within sheltered sites. We analysed COI sequence variation for 10 rocky intertidal invertebrate species, with a range of life histories, to test the hypotheses that larval type and habitat specificity are strong predictors of gene flow between biogeographic regions. Our data revealed that the southeast corner of Australia includes a strong barrier to gene flow for six of eight species with planktonic larvae, and a coalescence analysis of sequence differentiation (IM model) suggests that a barrier has existed since the Pleistocene. In contrast, two direct developers were not affected by the barrier. Our comparative approach and data from earlier studies (reviewed here) do not support the hypothesis that larval type predicts gene flow across this barrier, instead we found that the ability to utilize sheltered habitat provides a clearer explanation of the phylogeographic break. Indeed, the species that displayed little or no evidence of a phylogeographic break across the barrier each displayed unexpectedly relaxed habitat specificity.

A DIVERGENT mtDNA LINEAGE AMONG MESOPLODON BEAKED WHALES: MOLECULAR EVIDENCE FOR A NEW SPECIES IN THE TROPICAL PACIFIC? - Merel L. Dalebout; C. Scott Baker; Debbie Steel; Kelly M. Robertson; Susan J. Chivers; William F. Perrin; James G. Mead; Roger V. Grace; T. David Schofield (Marine Mammal Science, 2007)

Optimizing carbon sequestration in commercial forests by integrating carbon management objectives in wood supply modeling - Charles P.-A. Bourque; Eric T. Neilson; Chris Gruenwald; Samantha F. Perrin; Jason C. Hiltz; Yvon A. Blin; Geoffrey V. Horsman; Matthew S. Parker; Christie B. Thorburn; Michael M. Corey; Fan-rui Meng; D. Edwin Swift (Mitigation and Adaptation Strategies for Global Change, 2007)

A new mouse limb mutation identifies a Twist allele that requires interacting loci on Chromosome 4 for its phenotypic expression - Isabelle Blanc; Antoine Bach; Yvan Lallemand; Fabienne Perrin-Schmitt; Jean-Louis Gunet; Benot Robert (Mammalian Genome, 2003)

The effects of increasing CO 2 and temperature on oak leaf palatability and the implications for herbivorous insects - S. J. Dury; J. E. G. Good; C. M. Perrins; A. Buse; T. Kaye (Global Change Biology, 1998)
Rising levels of atmospheric CO 2 are expected to perturb forest ecosystems, although the extent to which specific ecological interactions will be modified is unclear. This research evaluates the effects of elevated CO 2 and temperature, alone and in combination, on the leaf nutritional quality of Pendunculate oak ( Quercus robur L. ), and the implications for herbiverous insect defoliators are discussed. A 3 °C temperature rise reduced leaf nutritional quality, by reducing foliar nitrogen concentration and increasing condensed tannin content. Doubling atmospheric CO 2 temporarily increased total phenolics, but also reduced leaf toughness. The nutritional quality of the second leaf flush (lammas growth) was considerably reduced at elevated CO 2 . It is concluded that larval development of spring‐feeding defoliators and hence adult fecundity may be adversely affected by increased temperatures.